Obesity and the Functional State of the Cardiovascular System in Children (Eurasian Medical Research Periodical, 2022)
Endothelial dysfunction (ED) is considered one of the pathogenetic mechanisms of a whole range of diseases. An effective way to diagnose ED is to detect specific biochemical markers in the blood that characterize the state of the vascular endothelium. The article highlights the pathogenetic role of a number of factors synthesized by endotheliocytes, the change in the level of which in biological fluids reflects a violation of the basic physiological properties of the endothelium: vasomotor function, angiogenesis regulation function, barrier and adhesive functions. In particular, the involvement of endothelin-1, von Willebrand factor, vasculo-endothelial growth factor (VEGF) and albuminuria is considered.